SUPERB final 3‐year outcomes using interwoven nitinol biomimetic supera stent - Garcia, Lawrence A.; Rosenfield, Kenneth R.; Metzger, Christopher D.; Zidar, Frank; Pershad, Ashish; Popma, Jeffrey J.; Zaugg, Margo; Jaff, Michael R.; Lei, Lanyu; Liu, Yuyin; Hadley, Gail L.; Arch, Victoria S. (Catheterization and cardiovascular interventions, 2017)
Importance Long‐term outcomes of an interwoven nitinol stent design represent the best in class for treatment of lower limb arterial obstructive disease Methods The subjects were enrolled in an open single arm study comparing the outcomes to an FDA mandated objective performance goal (OPG). Results About 325 patients (264 intention‐to‐treat and 64 roll‐in subjects) were enrolled. Mean follow‐up period was 887+/– 352 days. Treated lesion lengths were 7.8 cm ± 4.3 cm in the trial with chronic total occlusions comprising 24.6% (65/264) of subjects. Freedom from clinically driven target lesion revascularization (CD‐TLR) at 12 months was 89%, at 24 and 36 months it was 84% and 82% respectively. The difference in the 12 month CD‐TLR was 7% at 36 months. The difference of clinically driven‐TLR at 36 months in those subjects who received their stents deployed nominally in length, compressed or elongated (between −10% and +10% nominal length) had an impact on the CD‐TLR. At 2 and 3 years, freedom from CD‐TLR in minimal compression was 86.7%, and was 90.0% for moderate compression. In those stents deployed with minimal, moderate, or severe elongation (10–20%, 20–40%, or >40%, respectively) freedom from CD‐TLR of 84.1%, 87.4%, and 77.0% respectively at 12 months. At 2 and 3 years, freedom from CD‐TLR for moderate elongation was 81.8% and 78.2%, and for severe elongation was 63.4% and 42.3%, respectively. Fractures were distinctly uncommon with this stent with a single facture event in the 36 month follow‐up period. Discussion The interwoven nitinol design stent is a stent that achieves an excellent primary patency but further maintains the durability of the stent through 36 months. Optimal stent deployment remains critical to the performance of this stent device and requires optimal vessel preparation. © 2017 Wiley Periodicals, Inc.